2022
DOI: 10.1177/14771535221142812
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of non-image-forming effects of light in building design: A literature review

Abstract: Light affects many aspects of human physiology, through the non-image-forming (NIF) pathway. To account for this pathway, lighting design simulation tools need to combine several luminous and temporal factors to predict how architectural and lighting design decisions affect eye-level light exposure. Based on a systematic literature review, containing 55 journal and conference papers, the state-of-the-art towards implementing lighting beyond vision in computer simulation workflows for building design is present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 97 publications
(190 reference statements)
0
5
0
Order By: Relevance
“…Within each space, average illuminance values could also vary depending on view directions and the position of occupants (seating or standing), for instance. As suggested in recent research, 74,75 a broader interpretation of daily activities, as a temporal sequence of events, and daylight perception, [76][77][78] should therefore be considered when assessing daylight quality in various spaces. Yet, the novel modes of representation that spatialize melanopic light in relation to architecture, as polar coordinate diagrams and graphical displays of lighting pattern properties, inform designers on the incidence of architectural form and aperture typology on resulting light types, so as to guide future architectural design initiatives.…”
Section: Discussionmentioning
confidence: 99%
“…Within each space, average illuminance values could also vary depending on view directions and the position of occupants (seating or standing), for instance. As suggested in recent research, 74,75 a broader interpretation of daily activities, as a temporal sequence of events, and daylight perception, [76][77][78] should therefore be considered when assessing daylight quality in various spaces. Yet, the novel modes of representation that spatialize melanopic light in relation to architecture, as polar coordinate diagrams and graphical displays of lighting pattern properties, inform designers on the incidence of architectural form and aperture typology on resulting light types, so as to guide future architectural design initiatives.…”
Section: Discussionmentioning
confidence: 99%
“…To create a sustainable, good-performing lighting environment, a broad spectrum of design variables must be considered, i.e., building envelope properties, building services' systems, occupants' dynamic behaviour, and life-cycle costs. Lighting is one of these variables and must be balanced with many other, sometimes conflicting, performance objectives [1,2]. Earlier analysis and building performance simulations have shown that optimising building performance for energy and cost provides a great saving potential.…”
Section: Introductionmentioning
confidence: 99%
“…In light of the growing awareness of the profound impacts of beyond-vision effects on human health and well-being and according to the review done by Gkaintatzi-Masouti et al [1], new simulation workflows have been introduced to better predict and integrate these effects into the design and optimization of architectural environment by considering luminous and temporal factors of light, specifically light quantity, spectrum, directionality, timing, duration and previous light history [22]. These advanced simulation workflows provide practitioners and researchers with a detailed understanding of how lighting affects both the built environment and human occupants.…”
Section: Introductionmentioning
confidence: 99%
“…As has been intended and described by other authors [11,20,21], providing a simple process for smart or integrative lighting design is important when the process is properly integrated into a traditional workflow. Its implementation requires lighting designers to understand the tedious terminology defined, evaluated and correlated, when possible, to elucidate strengths and limitations to progress in its knowledge.…”
Section: Introductionmentioning
confidence: 99%